Chronic opioid use modulates human enteric microbiota and intestinal barrier integrity. (1st January 2021) - Cruz-Lebrón, Angélica; Johnson, Ramona; Mazahery, Claire; Troyer, Zach; Joussef-Piña, Samira; Quiñones-Mateu, Miguel E.; Strauch, Christopher M; Hazen, Stanley L.; Levine, Alan D.
ABSTRACT: Over the past three decades the United States has experienced a devastating opioid epidemic. One of the many debilitating side effects of chronic opioid use is opioid-induced bowel dysfunction. We investigated the impact of methadone maintenance treatment (MMT) on the gut microbiome, the gut bacterial metabolite profile, and intestinal barrier integrity. An imbalance in key bacterial communities required for production of short-chain fatty acids (SCFAs), mucus degradation, and maintenance of barrier integrity was identified. Consistent with dysbiosis, levels of fecal SCFAs were reduced in MMT. We demonstrated that metabolites synthesized by Akkermansia muciniphila modulate intestinal barrier integrity in vitro by strengthening the pore pathway and regulating tight junction protein expression. This study provides essential information about the therapeutic potential of A. muciniphila and warrants development of new clinical strategies that aim to normalize the gut microbiome in individuals affected by chronic opioid use.